O fluxo é indomável: narrativas sobre a Cracolândia - Rodrigues, Daniela Arcanjo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This monograph is a comparison between the covering made by the collective A Craco Resiste and Folha de São Paulo newspaper about Cracolândia, a travelling territory that was formed in the 1980's in Luz district. To make the analysis, were selected from May 14 to 28, 2017, a period that includes a mega-operation carried out by the Military Police of the State of São Paulo and the Metropolitan Civil Guard, which occurred on may 21. There was an escalation of violence against the flow at the time of removal. The main goal is to understand in which way a horizontal collective, created in a network society and using social media, can contribute to a more plural coverage in a commercial and printed newspaper. For the research, we considered all the units of information on the A Craco Resiste facebook page, main means of communication of the collective with its followers, and all the units of information of printed newspaper of Folha de São Paulo in the period. The text argumentative strategies, the chosen journalistic source, the organization of actions inside the context and the progression of facts and elements in every unit will be analyzed, in order to understand the narrative drawn by the two organizations over the two weeks. For a integral understanding of the research theme the following will be presented: the process of neglection from the State over the central region of the city (as a consequence of the migration of middle class and elite of the city to the West Zone); the Drug War; the conspicuous inequality of a country that had his foundations ruled by the slavery and the financialization of housing after 1980

Esta monografia é uma comparação entre a cobertura feita pelo coletivo A Craco Resiste e pelo jornal Folha de S. Paulo sobre a Cracolândia, território itinerante que se formou na década de 1980 no bairro da Luz. Para fazer a análise, foram selecionados os dias 14 a 28 de maio de 2017, período que engloba uma megaoperação realizada pela Polícia Militar do Estado de São Paulo e a Guarda Civil Metropolitana, que ocorreu no dia 21. Havia um acirramento da violência contra o fluxo na época da remoção. O objetivo principal é compreender de que forma um coletivo horizontal, criado na sociedade em rede e que faz uso de mídias sociais, pode contribuir para uma cobertura mais plural de um jornal comercial e impresso. Para a pesquisa, foram consideradas todas as unidades de informação da página no Facebook d'A Craco Resiste, principal meio de comunicação do coletivo com os seus seguidores, e todas as unidades de informação do jornal impresso da Folha de S. Paulo no período. Foram analisadas as estratégias argumentativas do texto, as fontes jornalísticas escolhidas, a organização das ações naquele contexto e a sucessão de fatos e elementos em cada unidade, para, então, compreender qual foi a narrativa traçada pelas duas organizações ao longo das duas semanas. Para ter um entendimento integral do tema da pesquisa serão apresentados o processo de abandono da região central da cidade pelo Estado (consequência da migração das classes médias e elites da cidade para a Zona Oeste); a Guerra às Drogas; a flagrante desigualdade de um país que teve sua fundação pautada pelo sistema escravocrata e o processo de financeirização da moradia após 1980
Keywords: Jornalismo; Pessoas desabrigadas; Drogas; Redução de danos; Damages; Cracolândia